Identification of a human-specific epitope in a conserved region of the La/SS-B autoantigen. - Weng, Y M (1993)
Human anti-La/SS-B autoantibodies are known to react with highly conserved epitopes suggested to be functional or active sites on the La/SS-B polypeptide. This study was designed to determine whether the autoantibodies also react with poorly conserved regions of La/SS-B as predicted by an antigen-driven autoimmune response. Binding of human autoantibodies to purified human, mouse, and bovine recombinant fragments representing immunodominant regions of the La/SS-B polypeptide was compared using Western blotting and ELISA. A cross-reactive epitope was located in the highly conserved NH2-terminal region of La/SS-B. Significantly, human-specific epitopes were identified in both the conserved RNA-recognition motif and a poorly conserved COOH-terminal fragment, providing direct evidence for an autoantigen-driven response. The lack of autoantibody cross-reactivity with a conserved domain of mouse and bovine La/SS-B implies that a small number of residues in human autoepitopes may be critical for autoimmunogenicity.